2019
DOI: 10.1111/cea.13478
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3‐like 1 drives allergic skin inflammation via Th2 immunity and M2 macrophage activation

Abstract: Background Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterized by defective skin barrier and Th2 immune responses. Chitinase 3‐like 1 (CHI3L1), also known as breast regression protein 39 (BRP‐39) in mice and human homologue YKL‐40, plays important roles in Th2 inflammation and allergen sensitization. CHI3L1 has been implicated in a variety of diseases including asthma characterized by inflammation, apoptosis and tissue remodelling, but its role in AD remains elusive. Objective The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…133 CHI3L1/YKL-40 promotes fibrotic process 133 and further accelerates Th2 deviation. 134 These results suggest a possibility that the scratch-induced IL-13Ra2 upregulation may convert the keratinocyte response from IL-13-dominant to CHI3L1/YKL-40-dominant pattern.…”
Section: Il-13ra2 and Scratch Injurymentioning
confidence: 76%
“…133 CHI3L1/YKL-40 promotes fibrotic process 133 and further accelerates Th2 deviation. 134 These results suggest a possibility that the scratch-induced IL-13Ra2 upregulation may convert the keratinocyte response from IL-13-dominant to CHI3L1/YKL-40-dominant pattern.…”
Section: Il-13ra2 and Scratch Injurymentioning
confidence: 76%
“…In particular, macrophages have been observed to accumulate in large amounts in the acutely and chronically inflamed skin of patients with atopic dermatitis, playing a key role in the pathogenesis of this disease. They exert proinflammatory functions like antigen-presenting phagocytosis and the production of inflammatory cytokines and growth factors, so contributing to the characteristic chronic inflammation of atopic dermatitis [13]. In a murine model of AD, the chitinase 3-like 1 protein was shown to affect Th2 inflammation, M2 macrophage activation, and skin barrier function [14].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are known to affect Th2 inflammation, and our previous study demonstrated that CHI3L1 is predominantly induced in macrophages during Th2-dependent skin inflammation. 19 We therefore used flow cytometric analysis to determine whether CHI3L1 is expressed in intestinal macrophages during food allergy. Strikingly, the population of CHI3L1-positive cells in intestinal macrophages was higher in the OVA-treated WT mice than in the control mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also indicated that CHI3L1 is involved in M2 macrophage polarization in atopic dermatitis and RSV infection. 19 43 This effect could be due to Th2 cytokines, such as IL-4 and IL-13, which are M2 polarization drivers. 45 Therefore, we suspect that increased expression of Th2 cytokines is involved in the development of the M2 phenotype, and that these synergistic effects may promote food allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation